Faktor-Faktor Yang Mempengaruhi Pengelolaan Aset Pemerintah Daerah - Rahmadani, Fitri; Maison, Witra; Defitri, Siska Yulia (Politeknik Raflesia Press, 2024)
This study aims to determine the Effect of Quality Apparatus on Asset Management, the Effect of Regulatory Understanding on Asset Management and Internal Control System on Asset Management, as well as the Effect of Quality Apparatus, Regulatory Understanding and Internal Control System simultaneously on Asset Management. This research was conducted on OPD in Solok City, namely Twenty-seven (27) OPD. The data used are primary data, the sample technique used is a saturated sample by distributing questionnaires. The sample in this study is the entire population, namely the Head of the OPD and the Head of the General Subdivision, and Managers of Goods of each OPD in the city of Solok. The results showed that Quality Aparatur, Regulatory Understanding and Internal Control System had a significant effect on Asset Management, then Quality Apparatus, Regulatory Understanding and Internal Control System had a simultaneous effect to Asset Management.